CHANGING PERCEPTION OF INDIA IN CHINESE IMAGINATION - Priyanka Keshry (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
China’s perception of India has shifted significantly over time. Initially, both countries shared anti-colonial sentiments after their respective independence movements, fostering a cooperative relationship, symbolised by the “Hindi-Chini Bhai Bhai” slogan. However, the 1962 Sino-Indian war and subsequent tensions, exacerbated by Cold War alignments, transformed China’s view of India from an ally to a rival. There is a perception in China that it is India who is nibbling with China and getting belligerent on border. Also some Chinese commentators now refer to India’s behaviour as “Ah Q-ism,” derived from Lu Xun’s novella The True Story of Ah Q, describing India’s actions as seeking symbolic moral victories despite facing setbacks in their border disputes with China